2019
DOI: 10.12688/f1000research.21235.1
|View full text |Cite
|
Sign up to set email alerts
|

Mortality risk factors among National Football League players: An analysis using player career data

Abstract: In general, National Football League (NFL) players tend to live longer than the general population. However, little information exists about the long-term mortality risk in this population. Frequent, yet mild, head trauma may be associated with early mortality in this group of elite athletes. Therefore, career playing statistics can be used as a proxy for frequent head trauma. Using data from Pro Football Reference, we analyzed the association between age-at-death, position, and NFL seasons-played among 6,408 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 9 publications
2
12
0
Order By: Relevance
“…Several of the lower SMRs in the former college player cohort are consistent with results in studies of former NFL players 25 , 26 , 27 , 28 , 29 , 52 and may be associated with the “healthy worker effect,” including regular exercise, physical activity, and lower cigarette smoking rates among male college athletes. 53 Results are also similar to those of recent studies of former professional soccer players in Scotland, 54 , 55 which found lower overall mortality and mortality from ischemic heart disease and lung cancer compared with the general population.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Several of the lower SMRs in the former college player cohort are consistent with results in studies of former NFL players 25 , 26 , 27 , 28 , 29 , 52 and may be associated with the “healthy worker effect,” including regular exercise, physical activity, and lower cigarette smoking rates among male college athletes. 53 Results are also similar to those of recent studies of former professional soccer players in Scotland, 54 , 55 which found lower overall mortality and mortality from ischemic heart disease and lung cancer compared with the general population.…”
Section: Discussionsupporting
confidence: 80%
“… 24 Despite the higher prevalence of CVD during life, mortality rate studies suggest that former National Football League (NFL) players live longer and have lower CVD mortality compared with men in the general US population, possibly because of greater physical activity and less cigarette smoking. 25 , 26 , 27 In contrast, former NFL players have been reported to have a greater risk of death from neurodegenerative causes, including ALS and Alzheimer disease. 28 , 29 Lehman and colleagues 29 examined mortality rates among 3439 former NFL players who played between 1959 and 1988 and found that although the former players had an overall lower mortality rate, neurodegenerative mortality was 3 times greater than that in the general US population; for ALS and Alzheimer disease, the rate was 4 times higher.…”
Section: Introductionmentioning
confidence: 99%
“…32 The variables included in the model were chosen a priori based on previous studies. 22,33 Players with missing data were eliminated from the regression analysis ( Figure). 33 The sensitivity analysis added player-fixed effects to the model, which did not substantially change the association between the pfCHII and mortality (eTable 6 in the Supplement).…”
Section: Discussionmentioning
confidence: 99%
“…The chief purpose of this quadratic term was to control for the confounding risk associated with a healthy (NFL) worker effect on hazard of death observed in the literature. 22,31,32 With this term, we obtained an estimate for the HR of the variable of interest, log of pfCHII, that was conditional on the healthy worker effect and, therefore, not survivorship biased. 22 Estimated concavity from the quadratic term was slight and mitigated only a low proportion of the reported increase in hazard associated with increases in the linear term pfCHII (eTable 7 in the Supplement).…”
Section: Discussionmentioning
confidence: 99%
“…Data was collected from Pro Football Reference, a free online database maintained by Sports Reference LLC that includes playing statistics from every player in NFL history, over 25,000 in total, with meticulously recorded data beginning in 1922 9 . Merged and transformed data is available from an open repository 10 . Variables of interest include birthdate, death date, position, and seasons-played.…”
Section: Methodsmentioning
confidence: 99%